The Effect Of Organizational Factors On Organizational Citizenship Behavior - Luthfi Aditya Hidayat; Elok Savitri Pusparini (Green Publisher Indonesia, 2025)
The phenomenon of fierce competition in the construction business and high turnover requires companies to attract and retain quality talent. This study analyzes the influence of Employer Brand Experience, Perceived Manager Support, Organizational Identification, and Career Focus HR Practices on Organizational Citizenship Behavior, with the mediating role of Employee Engagement. This study involved 396 organic permanent employees of PT XYZ as respondents and used the Structural Equation Modelling (SEM) method. The results show that Employer Brand Experience and Employee Engagement have a positive effect on Organizational Citizenship Behavior. Employer Brand Experience, Perceived Manager Support and Organizational Identification, Career Focus HR Practice have a positive effect on Employee Engagement. Employee Engagement has been proven to be able to mediate the relationship between Employer Brand Experience, Perceived Manager Support and Organizational Identification to Organizational Citizenship Behavior. The implication emphasizes the importance of employee involvement as the key to improving employee OCB behavior.